2007
DOI: 10.1007/s10350-006-0746-4
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Nerve Stimulation in Fecal Incontinence: Are There Factors Associated with Success?

Abstract: Patients with fecal incontinence from neurologic origins could be good candidates for sacral nerve stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
63
3
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 23 publications
7
63
3
12
Order By: Relevance
“…[14][15][16] Double incontinence represents a much more severe and stressful condition of pelvic floor dysfunction. 17 This explains why these patients always attained a marked statistical improvement in four domains of the SF-36 following permanent SNM.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Double incontinence represents a much more severe and stressful condition of pelvic floor dysfunction. 17 This explains why these patients always attained a marked statistical improvement in four domains of the SF-36 following permanent SNM.…”
Section: Discussionmentioning
confidence: 99%
“…12 For SNS, the implication of a peripheral neuropathy does not seem to predict failure of the technique. Gourcerol et al 13 found that a neurogenic cause of incontinence and abnormal sacral reflex testing was associated with a higher success of SNS. In our series, patients with an abnormal PNTML had no significant difference in their continence score at any time period up to 48 months compared with those who had normal PNTML.…”
Section: Discussionmentioning
confidence: 99%
“…16 Long-term clinical benefits and an increase in the number of responders would lead to a cost reduction in SNM therapy; indeed, in the long term, costs are likely to be comparable with those of conservative, sanitary and stoma therapies, even if comparative health costing in this area is difficult to determine because of the many factors that need to be taken into account. 17 A recent outcome and cost analysis of SNM for fecal incontinence has shown that it is highly effective.…”
Section: Discussionmentioning
confidence: 99%